A pilot study of a digital drainage system in pneumothorax. Issue 1 (4th November 2014) - Tunnicliffe, Georgia; Draper, Adrian
Abstract : Over recent years there has been increasing usage of digital systems within cardiothoracic surgery to quantify air leaks and aid in clinical decision-making regarding the removal of chest drains postoperatively. The literature suggests improved agreement on timing of removal of chest drains and a reduced length of stay of patients. It could be that such devices could be useful tools for the clinician managing cases of pneumothorax. Methods: This pilot study recruited adults admitted under the medical team with a pneumothorax requiring a chest drain. Participants had the underwater seal device changed for a digital device (Thopaz) which allowed continuous monitoring of the air leak. Drains were removed when either there was no ongoing air leak and the lung had expanded, or surgery was deemed necessary. Results: Thirteen patients with pneumothorax (four primary, nine secondary) used the device during their admission including one patient treated in the community (the device has internal suction). Data were used to aid the clinician in management of the pneumothorax including the timing of surgery/ removal of drain and commencement of suction. Discussion: Digital devices appear to be safe and effective and may prove to be a useful tool in the management of pneumothorax.